Social sciences in sport - Maguire, Joseph A. 1956- (Champaign, IL Human Kinetics, 2014)
Social Sciences in Sport presents discipline-specific knowledge in the social sciences, which aids in understanding the problems and potential of contemporary sport practices and experiences. This interdisciplinary reference provides in-depth coverage of sport studies and 14 social sciences, drawing connections across these disciplines to illuminate key issues and illustrate possibilities for change. Written by leading figures in the social sciences, the book synthesizes theory and research in social science and sport into four distinct areas: Identity, which discusses individual development and ethical considerations from history, philosophy, and psychology; Community, which considers anthropology, sociology, geography, and media studies when looking at sport in social groups; Capital, which draws research in status, wealth, power, and resources from economics, political science, and international relations; Governance, which discusses the enhancement of sport through law, social policy, management studies, and education; Organized around these topics into four parts, this reference places sport in the broader social sciences, showing where researchers in kinesiology and other disciplines can augment their knowledge base. Noting the range of issues and concerns in today's sport environment, readers will analyze the potential of a human development model in sport studies. Editor Joseph Maguire and an esteemed team of contributors present the evolution of sport in various social sciences. A stage-setting introduction explains the relevance of a social scientific perspective on sport and physical activity, and part introductions outline many relationships between the social sciences and sport. Chapters include a historical overview of the discipline or subject area, the core concepts and main theoretical perspectives in that area of expertise, critical findings, and the contemporary debates that characterize sport. Equipped with the social scientific knowledge and new perspectives from this essential collection, students and practitioners will be able to navigate classic and emerging issues in sport. Whether readers are social scientists considering sport as a subject of study or sport studies scholars attempting to make connections with the broader disciplines, Social Sciences in Sport promotes development of and through sport
Introduction: Making the Case for the Social Sciences of Sport, Exercise, and Health ; The Sport Ethic and the Natural Sciences ; Proposing a Human Development Model -- Part I. Identity: Definitions, Development, and the Individual -- Chapter 1. History of Sport / Wray Vamplew, PhD ; Relationships With Other Disciplines ; Core Concepts ; Main Theoretical Perspectives ; Critical Findings ; Key Debates ; Summary -- Chapter 2. Philosophy of Sport / Sigmund Loland, PhD, and Michael McNamee, PhD ; Historical Overview of the Discipline ; Main Theoretical Perspectives ; Key Debates ; Future Directions ; Summary -- Chapter 3. Psychology of Sport / David Lavallee, PhD, John Kremer, PhD, and Aidan Moran, PhD ; Core Concepts ; Main Theoretical Perspectives ; Critical Findings ; Key Debates ; Summary -- Part II. Community: Place, Space, Image, and the Social -- Chapter 4. Anthropology of Sport / Alan Klein, PhD ; Foundations in Sociocultural Anthropology ; Post-1970: The Athletic El Dorado and the Anthropologists Who Seek Him ; Looking Outward ; Summary -- Chapter 5. Sociology of Sport / Joseph Maguire, PhD ; Historical Development and Core Concepts ; Main Theoretical Perspectives ; A Sociological Account of Sport: Critical Findings ; Future Directions and Key Debates ; Summary -- Chapter 6. Geography of Sport / Christopher Gaffney, PhD ; Historical Trajectory of the Geography of Sport ; Core Concepts ; Main Theoretical Perspectives ; Key Debates and Critical Findings ; Future Directions ; Summary -- Chapter 7. Media Studies and Sport / David Rowe, PhD ; Historical Connections and Questions in Media Studies ; Understanding Media: Core Concepts ; Media Powers and Routines: Main Theoretical Perspectives ; Critical Findings and Key Debates in Sport and Media ; Conclusion: Sport and Media Studies in Transition -- Part III. Capital: Wealth, Power, and Resources -- Chapter 8. Economics and Sport / Stefan Szymanski, PhD ; Professional League Model: Theory and Policy ; Productivity Studies ; Economic Impact: Measurement, Theory, and Policy ; Sport, Physical Activity, and Well-Being ; Illustrations of Economic Issues ; Conclusions -- Chapter 9. Political Science and Sport / Jonathan Grix, PhD ; Core Concepts in Political Science ; Study of Sport and Politics ; Research Paradigms and Theoretical Perspectives in Political Science ; Applying Political Science and Sport: The Governance of Sport and the Politics of Mega-Events ; Summary -- Chapter 10. International Relations and Sport / Roger Levermore, PhD, and Aaron Beacom, PhD ; Core Concepts and Main Theoretical Perspectives ; Critical Findings and Key Debates ; Summary -- Part IV. Governance: Regulation, Organization, and Implementation -- Chapter 11. Sport and the Law / Deborah Healey, LLB, LLM (Hons) ; The Global Organization and Regulation of Sport ; Overview: The Place of Law in Sport ; Are the Courts Always Interested in Sport? ; Governance ; Aspects of Industry Self-Regulation in Sport ; Summary -- Chapter 12. Sport and Social Policy / Ramoń Spaaij, PhD ; Discipline of Social Policy: A Historical Overview ; Main Theoretical Perspectives ; Key Concepts ; Key Debates ; Summary -- Chapter 13. Sport and Management Studies / Lucie Thibault, PhD ; Sport as a Unique Industry ; Historical Overview ; Core Concepts ; Main Theoretical Perspectives ; Critical Findings ; Key Debates ; Summary -- Chapter 14. Sport and Education / Dawn Penney, PhD ; Core Concepts ; Theoretical Perspectives ; Critical Findings ; Key Debates ; Summary
Includes bibliographical references
Also available in print version
Keywords: Social sciences; Sports -- Anthropological aspects; Sports -- Psychological aspects; Sports -- Sociological aspects